The Effect of Cultural Differences on a Distant Collaboration for Social Innovation: A Case Study of Designing for Precision Farming in Myanmar and South Korea. (2nd January 2019) - Baek, Joon Sang; Kim, Soyoung; Harimoto, Taiei
Abstract: This paper explores the impacts of the ways in which cultural differences were encountered and negotiated during a collaboration between a Myanmar social enterprise and a South Korean university to design a soil sensor that enables farmers to more accurately measure soil qualities such as moisture, nutrient content, acidity, and temperature, thereby increasing productivity through irrigating and applying inputs more efficiently. Precision-farming technologies are expected to improve agricultural sustainability through producing more food with fewer resources at less cost, creating social impacts such as poverty alleviation. Soil sensors are a relatively new technology in both Myanmar and South Korea, two countries with significant socioeconomic and technological differences. When designers and engineers from these countries collaborated to develop new soil sensors and related services from a distance, these differences were magnified. For example, the Myanmar team approached the sensors as a social innovation whereas the South Korean team viewed them as a technological innovation, indicating differences in practices, mind sets, knowledge, value systems, design approaches to innovation, expected social impacts, and stakeholder outcomes. Concluding that an embrace of difference should be a condition for this collaboration, the paper discusses how these differences contoured this cross-cultural effort toward social innovation.